A IMPLEMENTASI MEDIA PEMBELAJARAN KOSBARAB UNTUK MENINGKATKAN KETERAMPILAN BERBAHASA ARAB KELAS X MA BAHRUL ULUM TAMBAK BERAS JOMBANG: IMPLEMENTASI MEDIA PEMBELAJARAN KOSBARAB UNTUK MENINGKATKAN KETERAMPILAN BERBAHASA ARAB KELAS X MA BAHRUL ULUM TAMBAK BERAS JOMBANG - Amalia, Rifda; Dian Rahmawati, Rina (PAI FAI UNHASY Tebuireng Jombang, 2023)
This KOSBARAB learning media is a media that appears with an Android model in which there is a creation of practice questions with Arabic vocabulary discussion material. The scope of the KOSBARAB application includes istima', qiro'ah, kalam, and khitabah. This application provides text, sound and image displays, making it easier for students to use it. The purpose of writing this paper is to find out more comprehensively about implementation, supporters and obstacles, as well as improving Arabic language skills for class X MA Bahrul Ulum Tambak Beras Jombang through the KOSBARAB learning media. The method determined by the researcher is a qualitative method. The results of this finding are in the form of an increase in students' ability to speak Arabic during Arabic language lessons because they can use the application in a fun way, but there are also several obstacles, such as there is a quiz on guessing words where the placement of the quiz questions is random among the material that has been provided, but it should be The quizzes are grouped according to the material list, and students also have difficulty pulling the buttons on the guess the word quiz.